Mendelian randomization of stroke risk after total hip and knee replacements - Pang, Liang; Zheng, Zhihui; Su, Pingping; Xu, Zhouhengte; Chen, Yirui; Liao, Zhicheng; Jia, Pengcheng; Zhang, Xiuling; Lv, Cunxian (Frontiers in Genetics, 2024)
Objective Previous epidemiological studies have indicated an increased risk of neurovascular diseases in patients following total hip and knee replacements. However, definitive conclusions regarding the increased risk of stroke post-replacement remain elusive. Therefore, we conducted a two-sample Mendelian randomization study to investigate the causal relationship between total hip and knee replacements and stroke. Methods We utilized summary data from publicly available genome-wide association studies (GWAS). Data concerning total hip replacements (THR, N = 319,037) and total knee replacements (TKR, N = 252,041) were sourced from the Genetics of Osteoarthritis (GO) Consortium. Stroke-related data were obtained from the International Stroke Genetics Consortium, encompassing any stroke (AS), any ischemic stroke (AIS), large vessel ischemic stroke (LV-IS), cardioembolic ischemic stroke (CE-IS), and small vessel ischemic stroke (SV-IS). Our primary causal inference method was the inverse variance weighted (IVW) approach, supplemented by weighted median and MR-Egger regression as secondary inference methods. We utilized the MR-PRESSO global test for outlier detection, Cochran’s Q statistic to assess heterogeneity, and assessed the multiplicity and stability of our findings using p-values from MR-PRESSO and MR-Egger regressions, and the leave-one-out method, respectively. Results We identified significant genetic associations between THR and both AS (IVW p = 0.0001, OR = 1.08, 95% CI = 1.04–1.12) and AIS (IVW p = 0.0016, OR = 1.07, 95% CI = 1.03–1.12). Significant associations were also observed between TKR and AS (IVW p = 0.0002, OR = 1.08, 95% CI = 1.04–1.12), as well as AIS (IVW p = 0.0005, OR = 1.15, 95% CI = 1.06–1.24). Conclusion Our findings genetically support an increased risk of stroke following total hip and knee replacements. However, further studies are necessary to elucidate the specific mechanisms underlying stroke episodes post-replacement.